Between universality of science and Western provincialism: Unveiling the “imperial gaze” of the Encyclopaedia of the Social Sciences (1930-1935) - Linos, Marie (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
This paper examines the imperial gaze that the social sciences could endorse during the interwar period, while attempting to establish themselves as a global field. It specifically focuses on the Encyclopaedia of the Social Sciences (ESS), an ambitious scholarly undertaking in the social sciences, edited by economists Alvin Johnson and Edwin Seligman. Fifteen volumes were published between 1930 and 1935 in total. By looking at the ESS’ contributors and articles, the paper questions the ambivalence between the universal appeal and rhetoric of this project and the actual outcome, which enforced a core/periphery division in the field of the social sciences. This indicates that, even if the ESS and its contributors defended a progressivist stance regarding colonialism, this scientific enterprise could not escape from the imperial culture that had deeply permeated US and European (social) science.